Mobile radiography at a music festival. Issue 8 (22nd July 2009) - Walker, A; Brenchley, J; Hughes, N
Abstract : Limb injuries are common at music festival sites and traditionally patients seen by on-site medical services require referral to hospital emergency departments for radiographic exclusion of bony injury. This takes clinical personnel off site, increases demand on local emergency departments and is inconvenient for revellers. This is an audit of the use of a portable digital radiography system at the Virgin music festival in Staffordshire over a 3-year period.